Postural biomechanical risks for nursing workersRiscos biomecânicos posturais em trabalhadores de enfermagem - Douglas Reis Abdalla; Fábio Sisconeto de Freitas; João Paulo Chieregato Matheus; Isabel Aparecida Porcatti de Walsh; Dernival Bertoncello
Introduction In the hospital environment, several types of professionals must be involved in continuous working shifts, under working conditions that are often unsatisfactory. Objective The objective of the present study was to analyze the biomechanical risk factors for work-related musculoskeletal disorders (WRMD). Material and methods This was a cross-sectional, exploratory, descriptive and quantitative study and its analysis considered 15 workers, in three shifts. A questionnaire containing personal information and general data regarding the work environment was applied. The REBA protocol was used for posture assessment, once the workers were recorded while performing their activities. The results were presented descriptively. Results In light of the results obtained, the working day was found excessive, particularly considering the weekly frequency and period of time of the working shifts. The REBA protocol showed that the positions adopted presented high risk for the development of WRMD in all nine activities evaluated. Conclusion The nursing activities were characterized as stressful for the workers involved.